Clinical characteristics of soybean allergy in Europe: A double-blind, placebo-controlled food challenge study - Ballmer-Weber, Barbara K.; Holzhauser, Thomas; Scibilia, Joseph; Mittag, Diana; Zisa, Guliana; Ortolani, Claudio; Oesterballe, Morten; Poulsen, Lars K.; Vieths, Stefan; Bindslev-Jensen, Carsten (Journal of allergy and clinical immunology, 2007)
Soybean is a relevant allergenic food, but little is known about individual threshold doses in soy allergy. We sought to determine the clinical characteristics of soy allergy in Europe, including a dose-response curve. Patients with a history of soy allergy underwent a titrated, double-blind, placebo-controlled food challenge. A statistical model was used to calculate the risk of allergic consumers to experience an allergic reaction to soy. Sera were analyzed for specific IgE to soy, peanut, Bet v 1, and Gly m 4. All patients but one responded primarily with subjective symptoms to the challenge followed by objective symptoms in 11 subjects, ranging from rhinitis up to a decrease in blood pressure. Cumulative threshold doses for allergic reactions ranged from 10 mg to 50 g for subjective symptoms and from 454 mg to 50 g for objective symptoms. The pattern of IgE reactivity against proteins with molecular weights of between approximately 10 and 70 kd was highly individual among the patients and did not correlate with the severity of symptoms. When data are fitted by using a normal distribution statistical model, they predict that 1% of patients with soy allergy would react subjectively and objectively with 0.21 and 37.2 mg of soy protein, respectively. Both the clinical and immunologic basis of soy allergy in Europe are highly complex, which affects the diagnosis of soy allergy and the advice given to patients with soy allergy in regard to risk management.